A study of the genus Protosticta Selys, 1855, with descriptions of four new species from Vietnam (Odonata: Platystictidae) - Phan, Quoc Toan; Kompier, Tom (Zootaxa, 2016)
The genus Protosticta Selys, 1855 from Vietnam is revised. Four new species, P. ngoai spec. nov., P. socculus spec. nov., P. pseudocuriosa spec. nov., and P. spinosa spec. nov. are described; detailed morphological structures of four species P. beaumonti Wilson, 1997 (dark form), P. caroli van Tol, 2008, P. grandis Asahina, 1995, and P. satoi Asahina, 1997, are provided. P. beaumonti is newly recorded for Vietnam. The female of P. caroli is described for the first time. P. linnaei van Tol, 2008, is also listed here, based on the original description and visual inspection of the type specimens. The occurrence of P. khaosoidaoensis Asahina, 1984, in Vietnam is reviewed and rejected. A total of nine Protosticta species have now been recorded for Vietnam.